Engineered EVs from LncEEF1G - overexpressing MSCs promote fibrotic liver regeneration by upregulating HGF release from hepatic stellate cells - Zhang, Jiebin; Qiu, Xiaotong; Lei, Yunguo; Chen, Haitian; Wu, Dongwei; Wang, Tingting; Sui, Xin; Xiao, Jiaqi; Jiang, Chenhao; Zhang, Huayao; Liu, Yasong; Liu, Xiaoquan; et al. (Experimental & molecular medicine, 2025)
Fibrosis is a disease that negatively affects liver regeneration, resulting in severe complications after liver surgery. However, there is still no clinically effective treatment for promoting fibrotic liver regeneration because the underlying hepatocellular mechanism remains poorly understood. Through microRNA microarrays combined with the application of AAV6, we found that high expression of miR-181a-5p in activated hepatic stellate cells (HSCs) suppressed the expression of hepatic growth factor (HGF) and partially contributed to impaired regeneration potential in mice with hepatic fibrosis that had undergone two-thirds partial hepatectomy. As nanotherapeutics, mesenchymal stem-cell-derived extracellular vesicles (MSC-EVs) have been verified as effective treatments for liver regeneration. Here we observe that MSC-EVs can also promote fibrotic liver regeneration via enriched lncEEF1G, which acts as a competing endogenous RNA to directly sponge miR-181a-5p, leading to the upregulated expression of HGF in HSCs. Finally, engineered MSC-EVs with high expression of lncEEF1G (lncEEF1G OE -EVs) were constructed, suggesting greater potential for this model. In summary, our findings indicate that lncEEF1G OE -EVs have a nanotherapeutic effect on promoting regeneration of fibrotic livers by modulating the miR-181a-5p/HGF pathway in HSCs, which highlights the potential of extracellular vesicle engineering technology for patients with hepatic fibrosis who have undergone hepatic surgery. Engineered mesenchymal stem cells that overexpress lncEEF1G can secrete extracellular vesicles that are rich in lncEEF1G (lncEEF1G OE -EVs). Upon injection of lncEEF1G OE -EVs into a fibrotic 70% partial hepatectomy mouse model, lncEEF1G competitively binds to miR-181a-5p in hepatic stellate cells, preventing the interaction between miR-181a-5p and the messenger RNA of hepatocyte growth factor. This consequently leads to an increase in the secretion of hepatocyte growth factor and the promotion of hepatocyte proliferation. Engineered extracellular vesicles enhance liver regeneration Partial hepatectomy is a common treatment for liver diseases, but liver fibrosis can hinder recovery. This study explores how mesenchymal stem-cell-derived extracellular vesicles (MSC-EVs) might help fibrotic livers regenerate after partial hepatectomy. Researchers found that MSC-EVs can boost liver regeneration by increasing hepatocyte growth factor production in hepatic stellate cells. The study uses a mouse model with liver fibrosis induced by carbon tetrachloride and then performed a partial hepatectomy. Researchers isolated MSCs from umbilical cords and extracted EVs from these cells. They injected these MSC-EVs into the mice and observed their effects on liver regeneration. MSC-EVs were found to be taken up by hepatic stellate cells, leading to increased hepatocyte growth factor production, which is crucial for liver cell proliferation. The results suggest MSC-EVs could be a promising treatment to enhance liver regeneration in fibrotic conditions. This summary was initially drafted using artificial intelligence, then revised and fact-checked by the author.